Single-nucleotide polymorphisms in dizygotic twin ovine fetuses are associated with discordant responses to antenatal steroid therapy - Erin L. Fee; Haruo Usuda; Sean W. D. Carter; Hideyuki Ikeda; Tsukasa Takahashi; Yuki Takahashi; Yusaku Kumagai; Michael W. Clarke; Demelza J. Ireland; John P. Newnham; Masatoshi Saito; Sebastian E. Illanes; et al. (BMC Medicine)
Abstract Background Antenatal steroid (ANS) therapy is given to women at risk of preterm delivery to accelerate fetal lung maturation. However, the benefit of ANS therapy is variable and how maternal and fetal factors contribute to this observed variability is unknown. We aimed to test the degree of concordance in preterm lung function, and correlate this with genomic, transcriptomic, and pharmacokinetic variables in preterm dizygotic twin ovine fetuses. Methods Thirty-one date-mated ewes carrying twin fetuses at 123 ± 1 days’ gestation received maternal intramuscular injections of either (i) 1 × 0.25 mg/kg betamethasone phosphate and acetate (CS1, n = 11 twin pairs) or (ii) 2 × 0.25 mg/kg betamethasone phosphate and acetate, 24 h apart (CS2, n = 10 twin pairs) or (iii) 2 × saline, 24 h apart (negative control, n = 10 twin pairs). Fetuses were surgically delivered 24 h after their final treatment and ventilated for 30 min. Results ANS-exposed female fetuses had lower arterial partial pressure of carbon dioxide (PaCO2) values than male fetuses (76.5 ± 38.0 vs. 97.2 ± 42.5 mmHg), although the observed difference was not statistically significant (p = 0.1). Only 52% of ANS-treated twins were concordant for lung maturation responses. There was no difference in fetal lung tissue or plasma steroid concentrations within or between twin pairs. Genomic analysis identified 13 single-nucleotide polymorphisms (SNPs) statistically associated with ANS-responsiveness, including in the proto-oncogene MET and the transcription activator STAT1. Conclusions Twin fetal responses and ANS tissue levels were comparable with those from singleton fetuses in earlier studies. Twin ovine fetuses thus benefit from ANS in a similar manner to singleton fetuses, and a larger dose of betamethasone is not required. Assuming no difference in input from the placental or maternal compartments, fetal lung responses to ANS therapy in dizygotic twin preterm lambs are dependent on the fetus itself. These data suggest a potential heritable role in determining ANS responsiveness.